Relationships among Children’s age, Caregivers’ Perceived Severity of Illness, Stress, Social Support and Quality of Life among Caregivers of Children with Congenital Heart Disease - Chanpa, Muslin; Sanasuttipun, Wanida; Srichantaranit, Arunrat (Nursing Science Journal of Thailand, 2018)
Purpose: To examine relationships between age of patients, severity of illness, stress, social support and quality of life among caregivers of children with congenital heart disease. Design: Correlational descriptive design. Methods: The study sample included 85 caregivers of children with congenital heart disease aged birth to 15 years attending at the Heart/Cardiovascular Center, Chiangrai Prachanukroh Hospital. The sample was selected by convenience sampling. Questionnaires were used in collecting data including 1) demographic data questionnaire 2) perception of severity of illness questionnaire 3) stress questionnaire 4) social support questionnaire and 5) quality of life questionnaire. Data were analyzed using descriptive statistics and Spearman’s rank-order correlation. Main findings: The study findings revealed that age of patients and severity of illness were not correlated with quality of life among caregivers of children with congenital heart disease (rs = .030, p = .39, and rs = - .127, p = .12, respectively). Stress was negatively and moderately correlated with quality of life among these caregivers (rs = - .574, p < .01). Social support was positively and moderately correlated with quality of life among these caregivers (rs = .603, p < .01). Conclusion and recommendations: According to the study findings, quality of life among caregivers of children with congenital heart disease was at a moderate level which was correlated with stress and social support. Therefore, healthcare team, especially professional nurses should assist these caregivers to reduce their stress and provide social support in all aspects in order to improve their quality of life.